2020
DOI: 10.1525/001c.12143
|View full text |Cite
|
Sign up to set email alerts
|

Policing and Racial (In)Justice in the Media: Newspaper Portrayals of the “Black Lives Matter” Movement

Abstract: The “Black Lives Matter” movement, centered on fighting racial injustice and inequality (particularly in the criminal justice system), has garnered a great deal of media attention in recent years. Given the relatively recent emergence of the movement, there exists very little scholarly research on media portrayals of the movement. In this article, I report findings from a qualitative examination of major newspaper portrayals of the Black Lives Matter (BLM) movement between April and August 2016, before the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…With the growing role of social media as a source of news (Anspach 2017;Boczkowski et al 2018;Fletcher and Nielsen 2018;Hopp et al 2020), videos of violence by police posted on social media have become an increasingly prominent source of hashtags and an impetus for mobilizing social justice movements (Anderson 2016;Bowman 2017;Clark et al 2017;Lake et al 2018). Social media sites such as Facebook are one means to rally the public (Miethe et al 2019), allowing users to discuss police brutality in online settings, independent of an incident's coverage in traditional media (Bordonaro and Willits 2018;Umamaheswar 2020). A bystander video posted on Facebook brought public attention to the killing of George Perry Floyd, Jr., in the twilight hours of Memorial Day, 25 May 2020.…”
Section: Introductionmentioning
confidence: 99%
“…With the growing role of social media as a source of news (Anspach 2017;Boczkowski et al 2018;Fletcher and Nielsen 2018;Hopp et al 2020), videos of violence by police posted on social media have become an increasingly prominent source of hashtags and an impetus for mobilizing social justice movements (Anderson 2016;Bowman 2017;Clark et al 2017;Lake et al 2018). Social media sites such as Facebook are one means to rally the public (Miethe et al 2019), allowing users to discuss police brutality in online settings, independent of an incident's coverage in traditional media (Bordonaro and Willits 2018;Umamaheswar 2020). A bystander video posted on Facebook brought public attention to the killing of George Perry Floyd, Jr., in the twilight hours of Memorial Day, 25 May 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Media coverage varies not only between sources with different political orientations, but also over time and between movements. For example, several studies found differences between the coverage of BLM protests in 2014-2016 and protests in earlier eras (Hopkins 2018, Steijns 2017, Umamaheswar 2020. We attend to the mutual relations between media and movements that lead to media attention cycles (Seguin 2016): activists intentionally seek to draw news coverage and success in gaining news coverage can lead to more protest.…”
Section: Methodsmentioning
confidence: 97%
“…Participant ages ranged from the "25 to 34 year-old" bracket all the way to "above 65 years old". We asked questions pertaining to personal and organizational experiences managing and mitigating violent repression during demonstrations, as well as the use of various technologies and tools in supporting tactics 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Although largely nonviolent, violent challengers like right-wing counter protesters and police reprisals invited violence by demonstrators that was latched onto by the media. This provided a springboard for opponents of the movement to cast the demonstrators as rioters and looters in an attempt to sway public opinion against them [1].…”
Section: Introductionmentioning
confidence: 99%